Kak nam obustroit' Rossiiu . Kak nam obustroit' Rossiiu . How Can We Improve Russia . Как нам обустроить Россию - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the Constitution of the Russian Federation; comparison of the Russian and U.S. Constitutions. Featured in the program: Boggs, Danny Julian (Judge of the United States Court of Appeals for the Sixth Circuit); Khripel', Gennadii Timofeevich (Politician); Pykhtin, Sergei Petrovich (Politician); Titov, Konstantin Alekseevich (Politician) Contributors: Lapina, Irina (Anchor) Обсуждение Конституции РФ. Сравнение Конституции РФ и США. В программе участвуют: Боггс, Дэнни Джулиан (Судья Апелляционного суда США шестого округа); Хрипель, Геннадий Тимофеевич (Политик); Пыхтин, Сергей Петрович (Политик); Титов, Константин Алексеевич (Политик) Создатели: Лапина, Ирина (Ведущий/Ведущая)